"How and when Chilean Pharmacology started to be experimental and became a science". (November 2015) - Bustos, Gonzalo; Renard, Georgina M.; Noriega, Viviana; Sotomayor-Zárate, Ramón
Abstract: Pharmacology in Chile has about 75 years of history and from its beginning until today has grown exponentially. Today, pharmacology is taught in the biomedical careers of the main Chilean universities and research centers in pharmacology are in the north, central and south of Chile. This editorial offers an overview of the main milestones that have led to the consolidation of Chilean pharmacology in Latin America and the world.